ENHANCING CUSTOMER SATISFACTION: UNRAVELING THE IMPACT OF SERVICESCAPE ELEMENTS ON GUEST EXPERIENCE - Adi, Ida Ayu Sri Puspa; Sekarti, Ni Ketut; Sulistyawati, Ni Ketut Sri; Mareni, Ni Ketut; Pastini, Ni Wayan (JURNAL KEPARIWISATAAN, 2025)
This study attempts to investigate the impact of servicescape—which includes ambient conditions (X1), spatial layout and functioning (X2), and artifacts, signs, and symbols (X3)—on guest satisfaction (Y) at Bali's five-star hotels. With 91 research participants who had stayed in five-star hotels in Bali, a multiple linear test was the statistical test technique employed. The study's findings demonstrate that ambient factors, which provide a comfortable environment for patrons, have a favorable and substantial impact on customer satisfaction. However, there was no discernible impact on spatial arrangement or functioning. This might be because different customers have different tastes when it comes to certain aspects of space layout and functionality. Signs, symbols, and artifacts have a positive and substantial influence, particularly in relation to the distinctiveness of Balinese architecture, according to another intriguing conclusion. The results of this study have practical consequences for hotel management, including ways to retain and develop artistic and cultural components in physical design, take into account the diversity of preferences for spatial arrangement and functioning, and increase the quality of ambient circumstances. In a market where there is competition, this might boost the hotel's brand image and maximize client happiness.